Outreach Vector Control Worker's Knowledge, Attitude and Practices Towards Mosquito Control and Associated Diseases - Shafia Saba; Unsar Naeem-Ullah; Shafqat Saeed; Ishtiaq A Rajwana; Alamgir Akhtar Khan (Tehran University of Medical Sciences, 2023)
Background: Mosquito Control Programs are articulated to control Mosquito Borne Diseases and success of such programs depends on the activities of field workers, and their adherence to the standard operating procedures (SOP's) is governed by their knowledge, attitudes, and practices (KAP). Present study was intended to assess the KAP of mosquito control workers of Pakistan to get an exact depiction of prevailing situation.   Methods: A cross-sectional descriptive study was conducted in March-April 2020. Questionnaire containing 30 closed and open-ended questions were administrated to participants. Knowledge and practices were evaluated using a scoring system i.e., by giving 1 point to each correct answer while attitude questions were analyzed individually and expressed in percentage for each response. Results: Total 639 workers were interviewed, mean age was 29.8 (SD ±7.87) years, majority (65.1%) was in age group of 18-30 years. Mean knowledge score was 6.96±1.28 (range 0-9) with 77.36% correct answers (P= 0.073). Mean practices score was 7.00±1.62 (range 2-9) with 77.83% appropriate answers (P< 0.001). Both knowledge and practices scores were higher for permanent employees, practices score increased with increase in job experience. Very weak positive correlation (r= 0.127) was observed between knowledge and practice scores. Conclusion: Appropriate practice correlates with better knowledge and positive attitude towards control activities. Hence, training on protection and protective measures for having a positive attitude among healthcare workers is necessary against the fight with mosquitoes.